2022
DOI: 10.1108/sasbe-08-2021-0144
|View full text |Cite
|
Sign up to set email alerts
|

Personal thermal comfort models: a deep learning approach for predicting older people’s thermal preference

Abstract: PurposeThis paper presents the development of personal thermal comfort models for older adults and assesses the models’ performance compared to aggregate approaches. This is necessary as individual thermal preferences can vary widely between older adults, and the use of aggregate thermal comfort models can result in thermal dissatisfaction for a significant number of older occupants. Personalised thermal comfort models hold the promise of a more targeted and accurate approach.Design/methodology/approachTwenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Their results highlighted that Deep Neural Network (DNN) achieved the highest accuracy of 78.01%, outperforming traditional models like Gradient Boosting and PMV. Finally, a study by Martins et al, [46] in 2022 emphasized the role of downsampling to address data imbalance. Their model, which considered parameters like health perception, showed that a DNN with health perception could achieve an accuracy of up to 91.67%.…”
Section: Studies Addressed Data Imbalance In Thermal Comfort Modelsmentioning
confidence: 99%
“…Their results highlighted that Deep Neural Network (DNN) achieved the highest accuracy of 78.01%, outperforming traditional models like Gradient Boosting and PMV. Finally, a study by Martins et al, [46] in 2022 emphasized the role of downsampling to address data imbalance. Their model, which considered parameters like health perception, showed that a DNN with health perception could achieve an accuracy of up to 91.67%.…”
Section: Studies Addressed Data Imbalance In Thermal Comfort Modelsmentioning
confidence: 99%
“…Arakawa Martins et al (2022) concentrate on indoor spaces, where we spend over 90% of our time exploring thermal comfort conditions as one of the core components of Indoor Environmental Quality (IEQ). With attention to personalised thermal comfort models, the study explores older adults' thermal comfort preferences using deep learning approaches.…”
mentioning
confidence: 99%